2021
DOI: 10.1002/alz.12424
|View full text |Cite
|
Sign up to set email alerts
|

What is paradoxical lucidity? The answer begins with its definition

Abstract: Paradoxical lucidity in dementia is a clinically significant but understudied phenomenon. A provisional definition was proposed by the 2018 National Institute on Aging expert workshop and published in Alzheimer's and Dementia. However, several conceptual features of this definition remain vague, creating barriers to robust clinical research. Here, we critically analyze the provisional definition and present a refined definition that can be applied in clinical research. The refined definition is based on an ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…Of course, we also need to address the elephant in the room: why does this phenomenon tend to happen prior to one's death? Peterson et al (2021) suggested that although the current statistics support terminal cases being the majority in paradoxical lucidity, biases of observation may also contribute to the numbers. However, considering many personal stories from caregivers, I personally do not think this is too much of a significant factor.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Of course, we also need to address the elephant in the room: why does this phenomenon tend to happen prior to one's death? Peterson et al (2021) suggested that although the current statistics support terminal cases being the majority in paradoxical lucidity, biases of observation may also contribute to the numbers. However, considering many personal stories from caregivers, I personally do not think this is too much of a significant factor.…”
mentioning
confidence: 76%
“…
Paradoxical lucidity in general refers to episodes of unexpected cognitive improvement in people with severe dementia, although the exact definition as well as the identification process are complicated and under debate (Peterson et al, 2021). Such patients are often believed to have lost the capacity for coherent communicative behaviors from irreversible brain damage.
…”
mentioning
confidence: 99%
“…1 Terminal lucidity, he asserts, "refers to any kind of unusually enhanced mental clarity before death," whereas paradoxical lucidity is mental clarity that occurs in persons with neurodegenerative diseases, such as This distinction contrasts with our assertion that all instances of terminal lucidity are paradoxical, but not all instances of paradoxical lucidity are also instances of terminal lucidity. 2 Nahm believes we are incorrect. Why?…”
Section: Is There a Difference Between Terminal Lucidity And Paradoxi...mentioning
confidence: 98%
“…Without further evidence and conceptual work to substantiate Nahm's argument, our original assertion that terminal lucidity is a type of paradoxical lucidity still stands. 2…”
Section: Has Nahm Accomplished This Conceptual Work?mentioning
confidence: 99%
“…1 Contrastingly, the second authors suggested that terminal lucidity should be regarded as an instance of paradoxical lucidity. 2 While I thoroughly appreciate that the subjects of terminal and paradoxical lucidity have found their way into professional medical research venues, a clarification regarding the precise meaning of these terms seems apt to avoid nurturing further misunderstandings. This clarification is of particular topicality because in several research projects that have recently been launched by the National Institute on Aging, the elaboration of more refined and detailed definitions for paradoxical lucidity is a crucial objective that is supposed to lay foundations for future research (for details, see NIA 3 ).…”
Section: E T T E R Terminal Lucidity Versus Paradoxical Lucidity: a T...mentioning
confidence: 99%